(untitled) (International Journal of Environmental Sciences, 2025)
A novel series of N-thiazol-2-yl-benzamide derivatives 3a-u was synthesized and evaluated in vivo for anticonvulsant,antidepressant, and antinociceptive activity. Anticonvulsant activity was assessed using the maximal electroshock andpentylenetetrazole-induced seizure tests in mice, with sodium valproate and phenytoin sodium as reference drugs. The majorityof compounds demonstrated robust activity against MES, and all exhibited promising activity against PTZ-induced seizures;compounds 3d and 3g provided complete protection. Acute neurotoxicity was evaluated using the rotarod test. Compounds3d and 3g exhibited the greatest potency without neurotoxicity compared to traditional pharmacotherapies. Compound 3dexhibited a median hypnotic dose of 867 mg/kg, approximately twice its TD50 value, while compound 3g displayed anHD50 of 632 mg/kg and an LD50 of 834 mg/kg. Compound 3d demonstrated significant antinociceptive activity (p <0.01) with an increased reaction time. The physicochemical properties and pharmacokinetic profiles of the target compoundswere also evaluated.